Process and consensus: ethical decision-making in the infertility clinic—a qualitative study. Issue 11 (30th October 2009) - Frith, L
Abstract : Infertility treatment is a speciality that has attracted considerable attention both from the public and bioethicists. The focus of this attention has mainly been on the dramatic dilemmas created by theses technologies. Relatively little is known, however, about how clinicians approach and resolve ethical issues on an everyday basis. The central aim of this study is to gain insight into these neglected aspects of practice. It was found that, for the clinicians, the process by which ethical decisions were made was of key importance. It will be argued that this focus on the process of decision-making is more than just empty proceduralism but is based on and facilitates certain substantive ethical principles. In conclusion, suggestions as to how ethical decision-making processes can be supported and improved in infertility practice will be made.